Pengaruh Motivasi Dan Preferensi Resiko Terhadap Minat Investasi Mahasiswa Universitas Hindu Indonesia Denpasar - Kusuma Dewi, Putu Arista; Cita Ayu, Putu; Bayu Putra, Cokorda Gde (Hita Akuntansi dan Keuangan, 2025)
One of the most popular forms of investment today is capital market investment. In this case, universities are a forum for students to learn about investment, one of which is the Indonesian Hindu University. However, students' financial knowledge when investing is still relatively low in minimizing risks in making investment decisions. The increasing issue of investment fraud targeting students is making young investors make investment decisions. The purpose of thies studiy was to determine the interaction of risk and motivation preference on the invesftment interesst of Indonesian Hindu University studentns in Denpasar. The population used in this study were all students of the Faculity of Economjics, Business and Tourism at the Hindu University of Indonesia from 2019 to 2022. The sample for this study was 332 students with a sampling technique using probability sampling including stratified random sampling. The findings of this study suggest that investment intention is positively and significantly influenced by motivation and positively and significantly influenced by perception of risk. The research results explain that the greater the motivation and risk perception, the higher the student's interest in investing. With this research, it is hoped that students will understand that there are risks that may occur and always follow the investment profits.